Repeated sessions of PACK-CXL WA for the treatment of resistant bacterial keratitis: a retrospective study - Mohammed M. Mahdy Tawfeek; Hanan Mohamed Abdel Hamid Ahmed; Ashraf Bor’i; Ahmed M. Nashaat Ali Rady (BMC Ophthalmology, 2023)
Abstract Objective The aim of this work is to evaluate the safety and efficacy of repeated sessions of photo-activated chromophore for keratitis-cross linking (PACK-CXL) window absorption (WA) for the treatment of resistant bacterial keratitis (BK). Patients and methods This is a retrospective clinical cohort study. Thirty eyes with clinically suspected and lab-confirmed bacterial keratitis, resistant to appropriate antibiotic therapy- which was modified by sensitivity reports- for 2 weeks with failure of epithelialization for 4 weeks after the standard anti-microbial therapy (SAT) together with one setting of PACK-CXL WA were included. If after the first session of PACK-CXL, there is a start of improvement in the form of reduction of the size of corneal ulcer and stromal infiltrates together with the start of epithelialization on clinical examination and AS-OCT, another session of PACK-CXL WA was performed after one week, and so on, till the complete healing and resolution of bacterial keratitis and confirmation by negative bacterial culture. Identification of the micro-organisms was done by lab study before and after treatment. Corneal healing was evaluated by corneal examination and anterior segment OCT (AS-OCT). Results Thirty eyes of 30 patients were recruited in this study. They were 16 males and 14 females, their mean age was 44.3 ± 5.38 years. The mean ulcer size was 3.96 ± 1.87 (mm3), while the mean size of stromal infiltrates was 4.52 ± 2.24 (mm3). PACK-CXL WA treatment was performed an average of 2.87 times for the 30 eyes. Complete healing and resolution (Successful treatment) was observed in 27 eyes (90%) of cases and failure of epithelialization was observed only in 3 eyes (10%). Complete corneal healing was reported in the second month postoperatively in 90% of eyes. Conclusion and recommendation PACK-CXL WA may be a promising, non-invasive treatment option for resistant bacterial keratitis. It may have a synergistic effect with standard antimicrobial treatment (SAT). Also, it can overcome the antibiotics resistance that has become rapidly spreading worldwide. Repeated sessions of PACK-CXL WA may be more effective for the treatment of resistant bacterial keratitis till complete epithelialization and resolution of BK than a single session with few complications. However, further prospective and comparative studies to support the results are needed.